please tell me how to factorise this equation
Attachments:
![](https://hi-static.z-dn.net/files/d2e/c092afb8832f4e8094303996862e945f.jpg)
Answers
Answered by
0
By observation, three of the roots are: 1, -1, -2.
Let the fourth root be z.
Since the sum of roots is -b/a = -5, so:
z + 1 - 1 - 2 = -5
z = -3
So, the roots are: 1, -1, -2, -3.
Hence, the factorized equation is: (x - 1)(x + 1)(x + 2)(x + 3)
vishalkumar2806:
where do you get this amazing observation
A quick glance over the coefficients of x^3 and x -> they're cancelling each other (+5, -5), so interchanging signs won't mess anything with x = 1, so x = -1 is also a root.
And it did.
So there.
Similar questions